Aquatic and human health risk assessment of Humanogenic Emerging Contaminants (HECs), Phthalate Esters from the Indian Rivers. (November 2022) - Elaiyaraja, Arun; Mayilsamy, Murugasamy; Vimalkumar, Krishnamoorthi; Nikhil, Nishikant Patil; Noorani, Peer Muhamed; Bommuraj, Vijayakumar; Thajuddin, Nooruddin; Mkandawire, Martin; Rajendran, Ramaswamy Babu
Abstract: Phthalate esters (PEs) one of the widely used plasticizers, and are known for their environmental contamination and endocrine disruption. Hence, it is important to study their distribution in a riverine environment. This study was aimed to determine the Spatio-temporal trends of 16 PEs in surface water, sediment and fish from rivers in southern India, and to assess their environmental health risks. Phthalates were quantified in all matrices with the mean concentrations (∑16 PEs) in water, sediment and fish as 35.6 μg/L, 1.25 μg/kg and 17.0 μg/kg, respectively. The Kaveri River is highly loaded with PEs compared to the Thamiraparani and Vellar Rivers. PEs such as DBP, DEHP, DCHP and DiBP were most frequently detected in all matrices, and at elevated concentrations in the dry season. The risk quotient (RQ < 1) suggests that the health risk of PEs from river water and fish to humans is negligible. However, DBP and DEHP from the Kaveri River pose some risk to aquatic organisms (HQ > 1). DEHP from the Vellar River may pose risks to algae and crustaceans. Non-priority phthalate (DiBP) may pose risks to Kaveri and Vellar River fish. The bioaccumulation factor of DCHP and DEHP was found to be very high in Sardinella longiceps and in Centropristis striata, and also exceeded the threshold limit of 5000 suggesting that PEs in the riverine environment may pose some health concerns. This is the first study to assess the spatio-temporal distribution, riverine flux and potential ecological effects of 16 PEs from the southern Indian Rivers. Graphical abstract: Image 1 Highlights: PEs were ubiquitously distributed in southern Indian rivers. DBP, DEHP, DCHP and DiBP were the predominant PEs. DiBP, DBP and DEHP may pose a risk (HQ > 1) to aquatic lives. Human dietary risk through drinking water and fish is negligible. The DCHP and DEHP were above the bioaccumulation criterion of 5000.